PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT (CRM) TERHADAP PRODUCT KNOWLEDGE DAN LOYALTY INTENTION PADA NASABAH PT. BANK BNI SYARIAH CABANG MATARAM - Magma Zulfiqar Ismail; Sulhaini Sulhaini; Handry Sudiartha Athar (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2019)
This study aims to determine the effect of Customer Relationship Management on Product Knowledge and Customer Loyalty Intention PT. Bank BNI Syariah Mataram Branch. And to find out the effect of Product Knowledge on Customer Loyalty Intention, PT. Bank BNI Syariah Mataram Branch. The type of research used is causality with a non purposive sampling technique. The population in this study is the customer of PT. Bank BNI Syariah Mataram Branch in the past year amounted to 100 respondents with data collection techniques using questionnaires. Data analysis uses path analysis with the help of Structural Equation Modeling (SEM) with AMOS Software.The results of the study show that; Customers Relationship Management (CRM) has a positive and significant effect on Product Knowledge at the BNI BNI Syariah Bank Branch. Product Knowledge has a positive and significant influence on consumer Loyalty Intention at the BNI BNI Syariah Bank Branch. Customers Relationship Management (CRM) has a positive and significant influence on consumer Loyalty Intention at the BNI BNI Syariah Bank Branch.Keywords : Customers Relationship Management (CRM), Product Knowledge dan Loyalty Intention